Minimalizacja ryzyka rynkowego przykładowej akcji przy uwzględnieniu warunkowej wariancji i kowariancji procesów - Humeńczuk, Piotr (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Two models to modeling conditional variances and covariances of two processes are presented. Two bivariate GARCH models are considered, one with conditional normal distribution of innovations and second with t-Student conditional distribution. They are used to estimate optimal, minimum-variance hedge ratios. An out-of-sample hedging strategy is implemented and the hedging effectiveness is measured. Dynamic models are found to give good description of the joint distribution of spot and futures returns but the hedging effectiveness is found to be low. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 185-193